IKLIM KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA PEGAWAI PADA INSTANSI KOMISI PEMILIHAN UMUM PROVINSI RIAU - Suprianti, Diana; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The organizational communication climate in the General Election Commission Agency of Riau Province is shaped through the aspects of the existing communication climate. The purpose of this study was to find out the aspects of the communication climate that existed in the Riau Provincial KPU agency, as well as knowing the perceptions of existing employee members of their institutions. This study used descriptive qualitative method. Data collection techniques used were interviews, observation, and documentation. The subjects in this study were members of the Riau Provincial KPU which were determined based on a purposive technique. The technique of interactive data analysis models is Miles and Huberman and uses the technique of checking the validity of the data, namely triangulation and extension of participation. The results of this study indicate that the organizational communication climate in Riau Provincial KPU agencies as a whole is going well, this can be seen from the aspect of support that is felt less by a handful of employees. The participatory decision-making aspect works well, because it always involves all members in taking. The aspect of trust, seen in the trust given by the leadership to the employees in entrusting every work done. The openness aspect in the Riau Provincial KPU agency that occurred between the head of the department and its employees had not run optimally. The objective aspect of high performance is felt by employees who have good performance, by getting awards. And the perceptions of employees of the Riau Provincial KPU agencies indicate that employees feel proud to be able to work in the Riau Provincial KPU agency. Keywords: Climate of Communication, Employee Performance